Performance of the two parasitoid species, Aphelinus varipes and Lysiphlebia japonica against sugarcane aphid, Melanaphis sacchari - Yuan-Qin Huang; Xiangbing Yang; Qing-Rong Bai; Sukhwinder Singh; Liang-De Tang; Lian-Sheng Zang (Biological Control)
Sugarcane aphid, Melanaphis sacchari Zehntner, is an important piercing-sucking pest on sorghum, sugarcane, and other graminaceous crops, not only damaging host plants by direct feeding, but also transmitting plant viruses that is detrimental to crop production. To evaluate the performance of two native parasitoid species, Aphelinus varipes (Förster) and Lysiphlebia japonica (Ashmead), on M. sacchari, the age stage, two-sex life table analysis was conducted to evaluate the demographic parameters of the two species. The results showed that the two parasitoids parasitized M. sacchari and completed their whole life history. The number of eggs laid by A. varipes (F: 209.49 offspring/female) and the number of oviposition days (Od: 14.18 d) were significantly higher than those of L. japonica (F: 87.47 offspring/female, Od: 3.36 d). Moreover, the intrinsic rate of increase (r), finite rate of increase (λ), and net reproductive rate (R0) of A. varipes (r: 0.3746 d-1, λ: 1.4160 d-1, R0: 113.125 offspring/individual) were significantly higher for A. varipes than those of L. japonica (r: 0.3386 d-1, λ: 1.4030 d-1, R0: 48.092 offspring/individual). In addition, the net killing rate (C0) of A. varipes was 119.57 (eggs/female), which was significantly higher than that of L. japonica (53.34 eggs/female). These findings suggested that A. varipes had higher performance with promising potential as biological control agent for sugarcane aphid.